Educational Potential of the Child's Out-of-School Experiences in the Opinion of Early Education Teachers - Ewa Kochanowska (Ignatianum University Press, 2023)
In this article, on the basis of research based on a qualitative strategy, an attempt was made to reconstruct the beliefs of early education teachers about children's out-of-school experiences and the need / possibility of using them in the practice of early childhood education. Teachers' ways of thinking about the features of children's out-of-school experiences and their value in the learning process at school are outlined. Getting to know the conceptualization of the studied area generated in the minds of teachers is very important due to their relationship with school practice, and more specifically with the design by teachers of didactic and educational situations aimed at integrating children's out-of-school experiences with the knowledge and experiences that are the subject of knowledge at school.The experiences gained in the extremely complex and dynamic contemporary space of a child's life are an important source of their knowledge and the basis of learning. The analysis of the collected statements of early childhood education teachers during individual open interviews with them allowed to identify the constitutive features of out-of-school experiences of children. Although teachers are aware of the continuity, multiplicity, transformation as well as the integrity and processuality of children's out-of-school experiences, in their statements they express caution in using them in educational activities at school due to their "imperfection". First of all, the teachers' way of thinking about the role of out-of-school experiences in the education of a child and, consequently, of school practice, requires changes.